1993
DOI: 10.1042/cs0850431
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Angiotensin II on Insulin Sensitivity: A Placebo-Controlled Study

Abstract: 1. There is evidence that hyperinsulinaemia increases the aldosterone response to angiotensin II, and that angiotensin-converting enzyme inhibitor drugs enhance peripheral glucose utilization, but the direct effects of angiotensin II on insulin sensitivity have not been reported previously. 2. In a randomized, double-blind, placebo-controlled, cross-over study, 12 healthy male subjects attended on 3 study days for the evaluation of the effects of a subpressor (1 ng min-1kg-1) and pressor (5 ng min-1kg-1) infus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…However, these results extend the observations of our own group and others who have recently reported the effects of various doses of ANG II on insulin sensitivity in lean healthy male volunteers (12)(13)(14)(15). In our own hands, using an experimental protocol identical to that described here, 5 ng-kg" 1 -min" 1 of ANG II produced a small, sustained increase in BP (11/9 mmHg), but neither this dose nor 1 ng • kg" 1 • min" 1 of ANG II affected glucose uptake under hyperinsulinemic conditions (12).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, these results extend the observations of our own group and others who have recently reported the effects of various doses of ANG II on insulin sensitivity in lean healthy male volunteers (12)(13)(14)(15). In our own hands, using an experimental protocol identical to that described here, 5 ng-kg" 1 -min" 1 of ANG II produced a small, sustained increase in BP (11/9 mmHg), but neither this dose nor 1 ng • kg" 1 • min" 1 of ANG II affected glucose uptake under hyperinsulinemic conditions (12).…”
Section: Discussionsupporting
confidence: 92%
“…Contrary to general expectations, there was evidence that ANG II in doses sufficient to cause a rise in BP led to an increase in insulin-stimulated glucose transport (14,15). Subpressor and weak-pressor doses of ANG II, although increasing plasma ANG II concentrations more than twofold, had no effect on insulin sensitivity (12,13). The mechanism of this effect has not been clearly resolved, but because ANG II appeared to have parallel dose-dependent effects on glucose uptake and BP, with evidence of redistribution of blood flow to skeletal muscle (14), a hemodynamic mechanism rather than a direct biochemical effect has been proposed (14,15).…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…Morris et al [34] and Townsend et al [35] did not observe changes in the rate of glucose disposal in healthy subjects during infusion of low-dose angiotensin II (5 and 10 ng ⋅ kg −1 ⋅ min −1 ). Subsequently, the same authors, using higher doses of angiotensin II (15 ng ⋅ kg −1 ⋅ min −1 ), found that this peptide increases the rate of glucose disposal and therefore insulin sensitivity both in healthy [11] and non-insulin-dependent diabetic subjects [12].…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically this could explain the effects seen with ACE inhibitors but it is then difficult to explain why other vasodilator drugs have no effect on glucose transport. Although angiotensin II has no effect on insulin sensitivity, at least in normal subjects [47], increased kinin levels following ACE inhibition enhance glucose transport [48].…”
Section: Angiotensin Converting Enzyme (Ace) Inhibitorsmentioning
confidence: 99%